Pengaruh kepribadian big five terhadap self-disclosure dalam konteks second account Instagram - Hadyana, Roezha (Maliki Interdisciplinary Journal, 2026)
This research is motivated by the phenomenon of second accounts, which are considered to provide a safe private space for individuals to express themselves more freely. As a result, an individual’s level of self-disclosure is suspected to be influenced by their personality type. The purpose of this study is to examine the influence of the Big Five personality traits on self-disclosure among Instagram second account users. A quantitative approach using linear regression analysis was employed, involving 101 female students of UIN Maulana Malik Ibrahim Malang who own a second Instagram account. The instruments used were the Big Five Inventory (BFI) to measure the five personality dimensions and the Revised Self-Disclosure Scale (RSDS) to assess the individuals’ level of self-disclosure.The findings show that only two personality dimensions have a significant influence on self-disclosure: openness to experience and neuroticism. This indicates that openness to new experiences and emotional sensitivity are key predictors of self-disclosure among second account users. Meanwhile, extraversion, agreeableness, and conscientiousness do not have a significant effect. This means that social skills, friendliness, and self-control do not directly influence an individual’s level of self-disclosure. Overall, this study highlights that self-disclosure on Instagram second accounts is more closely related to emotional needs and self-exploration rather than the motivation to interact with others.